Association between Folic Acid Supplementation and Hypertensive Disorder Complicating Pregnancy in Jiangsu Province: A Cross-Sectional Study. (6th September 2022) - Cong, Jing; Pu, Danhua; Tan, Rongrong; Ge, Xiaoyun; Zhu, Weipei; Shen, Cai-e; Ge, Jianfen; Luo, Xiucui; Liu, Juan; Wu, Jie
Abstract : Objectives . To investigate the association of folic acid (FA) supplementation with hypertensive disorder complicating pregnancy (HDCP) and preeclampsia in Jiangsu Province, China. Materials and Methods . In this cross-sectional study, a total of 10, 662 women with infants born between January 2017 and December 2018 were enrolled in Jiangsu Province, China. Maternal women with and without FA supplement intake were compared in this study. FA supplementation included 0.4 mg FA (0.4 FA), multivitamins with 0.4 mg FA (multivitamin (MV)+0.4 FA), and multivitamins with 0.8 mg FA (MV + 0.8 FA). Associations between FA intake, FA supplement dose or duration, (MV + FA) dosage per weight, and HDCP were analysed using ANOVA, the chi-square test, and logistic regression analysis. Results . Over the study follow-up period, the incidences of HDCP and preeclampsia were 3.5%, 1.4%, and 2.2%, 0.6% in the non-FA supplementation and FA supplementation groups, but only 1.5% and 0.1% in the MV + 0.8 FA group in early pregnancy. Compared with the non-FA group, HDCP and preeclampsia had the lowest risk in the MV + 0.8 FA group among the seven FA supplementation groups (HDCP: RR = 0.42, 95% CI = 0.27-0.68, P = 0.001 ; preeclampsia: RR = 0.09, 95% CI = 0.03–0.33, P = 0.001 ) in early pregnancy. Compared with the 0.4 FA alone group, the risk of HDCP and preeclampsia in women taking MV + 0.8 FA was significantly reduced (RR = 0.60, 95% CI = 0.41–0.87, P = 0.008 ; preeclampsia: RR = 0.18, 95% CI = 0.06–0.60, P = 0.005 ) in early pregnancy. (MV + FA)/BMI supplementation was associated with the risk of HDCP in early pregnancy (P trend = 0.002). Conclusions . MV supplement with 0.8 mg FA during early pregnancy may be effective in reducing HDCP and preeclampsia risk. The study provided the viewpoint that (MV + FA)/BMI could be used as a reference for FA intake in pregnant women of different weights.